Colloidal Bismuth Chalcohalide Nanocrystals. Issue 22 (10th March 2022) - Quarta, Danila; Toso, Stefano; Giannuzzi, Roberto; Caliandro, Rocco; Moliterni, Anna; Saleh, Gabriele; Capodilupo, Agostina‐Lina; Debellis, Doriana; Prato, Mirko; Nobile, Concetta; Maiorano, Vincenzo; Infante, Ivan; et al.
Abstract: Here we present a colloidal approach to synthesize bismuth chalcohalide nanocrystals (BiEX NCs, in which E=S, Se and X=Cl, Br, I). Our method yields orthorhombic elongated BiEX NCs, with BiSCl crystallizing in a previously unknown polymorph. The BiEX NCs display a composition‐dependent band gap spanning the visible spectral range and absorption coefficients exceeding 10 5  cm −1 . The BiEX NCs show chemical stability at standard laboratory conditions and form colloidal inks in different solvents. These features enable the solution processing of the NCs into robust solid films yielding stable photoelectrochemical current densities under solar‐simulated irradiation. Overall, our versatile synthetic protocol may prove valuable in accessing colloidal metal chalcohalide nanomaterials at large and contributes to establish metal chalcohalides as a promising complement to metal chalcogenides and halides for applied nanotechnology. Abstract : A reliable and versatile colloidal synthetic method to prepare mixed anion semiconductor nanocrystals of the V–VI–VII group, namely bismuth chalcohalides, is presented. The chemical stability and the optical absorption properties of the colloidal bismuth chalcohalide nanocrystals may set this class of materials as a promising complement to metal chalcogenides and halides for solution‐processed light‐harvesting purposes.